2016
DOI: 10.1016/j.ultsonch.2015.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultrasonic treatment on total phenolic extraction from Lavandula pubescens and its application in palm olein oil industry

Abstract: The aims of the current study were to evaluate the best technique for total phenolic extraction from Lavandula pubescens (Lp) and its application in vegetable oil industries as alternatives of synthetic food additives (TBHQ and BHT). To achieve these aims, three techniques of extraction were used: ultrasonic-microwave (40 kHz, 50 W, microwave power 480 W, 5 min), ultrasonic-homogenizer (20 kHz, 150 W, 5 min) and conventional maceration as a control. By using the Folin-Ciocalteu method, the total phenolic conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 40 publications
(45 reference statements)
0
24
0
Order By: Relevance
“…It is quite evident from results of current study that increased time of sonication resulted in the elevation of total antioxidant activity due to increased cellular damage. This increase in amount of total phenolics and flavanols are helpful in curtailing various metabolic syndromes, as these compounds possess significant anti‐oxidative properties (Rashed et al, ). Applications of ultra‐sonication and thermo‐sonication have been reported to increase the content of anti‐oxidative properties of various fruit juices (Bhat et al, ; del Socorro Cruz‐Cansino et al, ; Santhirasegaram, Razali, & Somasundram, ; Zou & Hou, ).…”
Section: Resultsmentioning
confidence: 99%
“…It is quite evident from results of current study that increased time of sonication resulted in the elevation of total antioxidant activity due to increased cellular damage. This increase in amount of total phenolics and flavanols are helpful in curtailing various metabolic syndromes, as these compounds possess significant anti‐oxidative properties (Rashed et al, ). Applications of ultra‐sonication and thermo‐sonication have been reported to increase the content of anti‐oxidative properties of various fruit juices (Bhat et al, ; del Socorro Cruz‐Cansino et al, ; Santhirasegaram, Razali, & Somasundram, ; Zou & Hou, ).…”
Section: Resultsmentioning
confidence: 99%
“…Ultrasound-assisted extraction is performed with a probe ultrasonic processor. It extracts the active components into the solvent through ultrasonic vibration and cavitation[ 19 ]. Several studies have indicated that many factors, including the particle size, solvent, solid/solvent ratio, temperature, extraction time, liquid height and duty cycle of ultrasound exposure exert significant effects on the extraction yield of beta-carotene[ 17 , 18 ].…”
Section: The Extraction and Synthesis Of Beta-carotenementioning
confidence: 99%
“…The scavenging activity of Foshou fruit extract against DPPH • was determined according Rashed et al [27] with a slight modification according DPPH • methanolic solution (3.5 mL, 60 µM) was added to 300 µL of Foshou fruit extract. After shaking, the reaction was carried out in the dark at room temperature.…”
Section: Determination Of Antioxidant Activity By Dpph • -Sa Assaymentioning
confidence: 99%